Probing the potential of rare earth elements in the development of new anticancer drugs: single molecule studies - Batista, Josiane A. D.; de Oliveira, Rayane M.; Lima, Carlos H. M.; Lana Júnior, Milton L.; dos Anjos, Virgílio C.; Bell, Maria J. V.; Rocha, Márcio S. (Beilstein Journal of Nanotechnology, 2025)
We use optical tweezers and atomic force microscopy to investigate the potential of rare earth elements to be used as anticancer agents in the development of new chemotherapeutic drugs by characterizing the binding of three rare earths (ytterbium, neodymium, and erbium) to double-stranded DNA, which is one of the main targets for these drugs inside cells. The three elements presented a significant interaction with the biopolymer in buffers of physiological relevance, typically binding with very high equilibrium association constants (106 to 107 M−1) at the DNA grooves. Furthermore, neodymium and erbium can also induce a very strong compaction/condensation of the double helix at high concentrations, promoting DNA collapse at the single molecule level in a similar way to what occurs with classical DNA condensing agents such as polycations and depletants.
Keywords: DNA; optical tweezers; rare earth elements; single molecule force spectroscopy